The Impact of Value Chain Financing on Profitability for South Africa’s Edible Oil Manufacturing Companies: Raw Materials and Working Capital Approaches - Aliamutu, Kansilembo; Mkhize, Msizi (Journal of Economics and Behavioral Studies, 2024)
Edible oil manufacturing companies in South Africa generate significant amounts of revenue, which they do not capitalize on. South Africa has no shortage of consumer demand for commodities. The edible oil sector is hampered by poor raw material output in the nation, insufficient financing by value-chain participants, and a shortage of specific effort and understanding in growing the value chain. The research aim was to evaluate the impact of value chain financing on profitability for South Africa’s edible oil manufacturing companies via raw materials and working capital approaches. Utilizing secondary data collected from the financial statements of edible oil manufacturing companies from 2012 to 2022. Throughout the research, a positivism paradigm was applied using a descriptive retrospective panel data approach. Multiple regression analysis was used to determine the connection between the value chain financing variables (raw materials as well as working capital) and the profitability of edible oil manufacturing companies in South Africa. On financing in raw material there was a negative correlation among the two variables, but it is not statistically significant (r = -0.030, p =.424). On financing in working capital, there was a positive correlation (r =.201, p =.012), the connection between financing in creditors management and profitability in the edible oil company has a positive correlation (r =.162, p = 0.09) but is not statistically significant. The research found that raw material financing and working capital financing had no statistically significant connection to the profitability of edible oil manufacturing companies in South Africa.